1999
DOI: 10.1016/s0735-1097(99)00065-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in endothelial function by angiotensin-converting enzyme inhibition in non–insulin-dependent diabetes mellitus

Abstract: In type II diabetic subjects without evidence of vascular disease, the ACE inhibitor enalapril improved stimulated and basal NO-dependent endothelial function. The study extends the spectrum of beneficial effects demonstrated to result from ACE inhibition in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
105
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 38 publications
5
105
0
Order By: Relevance
“…The reasons for the increased risk are unclear but may be related to several abnormalities, the most prominent of which appears to be endothelial dysfunction (7). ACE inhibitors have been shown to have a beneficial effect on improving vascular reactivity (8). However, we have recently demonstrated that in African American patients with proteinuria that persists despite optimal ACE inhibitor therapy, endothelial function is severely impaired compared to both matched patients whose proteinuria resolved as well as similarly affected Non-Hispanic whites .…”
Section: Introductionmentioning
confidence: 97%
“…The reasons for the increased risk are unclear but may be related to several abnormalities, the most prominent of which appears to be endothelial dysfunction (7). ACE inhibitors have been shown to have a beneficial effect on improving vascular reactivity (8). However, we have recently demonstrated that in African American patients with proteinuria that persists despite optimal ACE inhibitor therapy, endothelial function is severely impaired compared to both matched patients whose proteinuria resolved as well as similarly affected Non-Hispanic whites .…”
Section: Introductionmentioning
confidence: 97%
“…Over the past several years, a number of studies have implicated an important role for the renin-angiotensin system in the pathogenesis of cardiovascular abnormalities associated with T1D. For example, investigators have shown that tissue and plasma levels of angiotensin converting enzyme (ACE) and angiotensin II are elevated in diabetic subjects and animals (Duntas et al, 1992;HarrisonBernard et al, 2002;Lieberman and Sastre, 1980;Schernthaner et al, 1984) and treatment of diabetic subjects with ACE inhibitors can improve impaired NOS-dependent responses of large peripheral vessels (Arcaro et al, 1999;Cheetham et al, 2000;O'Driscoll et al, 1997;O'Driscoll et al, 1999). In addition, we (Trauernicht et al, 2003) have shown that treatment of diabetic rats with an ACE inhibitor (enalapril) could alleviate impaired eNOS-dependent responses of cerebral arterioles during T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibition improves both of these prognostic markers in diabetes [13,14] and is also associated with an improvement in morbidity and mortality in diabetic subjects [15]. It is thought that ACE inhibitors beneficially affect these parameters by reducing angiotensin II bioactivity [16,17].…”
Section: Introductionmentioning
confidence: 99%